Analysis of missing values in simultaneous linear functional relationship model for circular variables - Hassan, S.F.; Zubairi, Y.Z.; Hussin, A.G. (2009)
Circular data is rather special and it cannot be treated just like linear data. Hence, all existing procedures that have been used in treating the missing values in linear data are not longer available for circular data. Imputation methods for missing values data are proposed in the paper. Two different methods namely circular mean by column and sample mean are used. For this study, missing values were tested in parameter estimation for simultaneous linear functional relationship model for circular variables. Via simulation studies, it shows that the proposed method provide an adequate approach in handling missing values for circular variables.